2023
DOI: 10.1186/s12944-023-01978-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted changes in blood lipids improves fibrosis in renal allografts

Yang-He Zhang,
Bin Liu,
Qingfei Meng
et al.

Abstract: Background Chronic interstitial fibrosis is the primary barrier against the long-term survival of transplanted kidneys. Extending the lifespan of allografts is vital for ensuring the long-term health of patients undergoing kidney transplants. However, few targets and their clinical applications have been identified. Moreover, whether dyslipidemia facilitates fibrosis in renal allograft remains unclear. Methods Blood samples were collected from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Moreover, we observed an anti-fibrotic action of the lower, but not the higher FF dose only in young rats. This result aligns with reports of FF’s renal anti-fibrotic effects in rodent models of HFD [ 25 ], diabetes [ 6 , 27 , 31 ], ischemia-reperfusion injury [ 32 ], and renal transplants [ 33 , 34 ]. Indeed, it has been suggested that renal lipotoxicity due to elevated blood lipid levels causes transcriptional suppression of PPARα by ATF6α (Activating Transcription Factor 6 alpha), leading to increased expression of connective tissue growth factor involved in fibrosis [ 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, we observed an anti-fibrotic action of the lower, but not the higher FF dose only in young rats. This result aligns with reports of FF’s renal anti-fibrotic effects in rodent models of HFD [ 25 ], diabetes [ 6 , 27 , 31 ], ischemia-reperfusion injury [ 32 ], and renal transplants [ 33 , 34 ]. Indeed, it has been suggested that renal lipotoxicity due to elevated blood lipid levels causes transcriptional suppression of PPARα by ATF6α (Activating Transcription Factor 6 alpha), leading to increased expression of connective tissue growth factor involved in fibrosis [ 32 ].…”
Section: Discussionsupporting
confidence: 90%